2002
DOI: 10.1590/s1676-06032002000200015
|View full text |Cite
|
Sign up to set email alerts
|

Reprodução do falcão-de-coleira Falco Femoralis Temminck 1822 (Falconiformes: Falconidae) no município de Juiz de Fora, sudeste do Brasil

Abstract: De junho de 1998 a dezembro de 1999, cinco eventos reprodutivos do falcão-de-coleira Falco femoralis foram registrados e monitorados no município de Juiz de Fora, Estado de Minas Gerais, sudeste brasileiro. Dois ninhos encontrados em 1998 foram monitorados por duas estações reprodutivas (1998/99), enquanto um terceiro, encontrado em 1999, foi monitorado apenas em uma estação reprodutiva. Todos os ninhos estavam situados em árvores isoladas, localizadas em áreas de pastagens, e a altura em relação ao solo, vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
1
5
0
2
Order By: Relevance
“…Though detailed food habit and foraging studies have been published for some Brazilian raptors (e.g., Motta-Junior & Bueno 2004, Sazima 2007, Granzinolli & Motta-Junior 2007 data on most species are scarce (see reports on Brazilian species in compilations such as könig et Ferguson-Lees &Christie 2001). Breeding studies on Brazilian raptors are even more difficult to find, with few specific published studies (e.g., Granzinolli et al 2002, Lopes et al2004, Carvalho-Filho et al 2005, Specht et al 2008, and scattered information in Sick (1997). Mobbing by birds against raptors is assumed to be an anti-predator adaptation (Curio et al 1978), and virtually no specific study has addressed this topic in Brazil, except by some observations in Motta-Junior (2007) and Cunha et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Though detailed food habit and foraging studies have been published for some Brazilian raptors (e.g., Motta-Junior & Bueno 2004, Sazima 2007, Granzinolli & Motta-Junior 2007 data on most species are scarce (see reports on Brazilian species in compilations such as könig et Ferguson-Lees &Christie 2001). Breeding studies on Brazilian raptors are even more difficult to find, with few specific published studies (e.g., Granzinolli et al 2002, Lopes et al2004, Carvalho-Filho et al 2005, Specht et al 2008, and scattered information in Sick (1997). Mobbing by birds against raptors is assumed to be an anti-predator adaptation (Curio et al 1978), and virtually no specific study has addressed this topic in Brazil, except by some observations in Motta-Junior (2007) and Cunha et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, its nesting has been studied in detail in the Atlantic Forest by Granzinolli et al (2002) but not in other regions. For example, no study examined its breeding in the Cerrado, where only their feeding ecology (Silveira et al 1997) and habitat use (e.g., Antas & Cavalcanti 1988, Tubelis & Cavalcanti 2001, Pacheco & Olmos 2010 have been studied.…”
mentioning
confidence: 99%
“…This is because Montoya et al (1997) reported a preference for Yucca elata trees in Mexican desert grasslands, considering a sample of seven nests. Other studies have not identified the plant species used for nesting or involved a few nests, not being able to identify a choice (e.g., de Lucca & Saggese 1996, Granzinolli et al 2002, Macías-Duarte et al 2004, Meyer & Williams 2005. Also, studies that investigated nestsite selection by these falcons examined physical nest-site characteristics, but not the plant species used for nesting (e.g., Brown & Collopy 2008).…”
mentioning
confidence: 99%
“…As maiores abundâncias de B. albicaudatus coincidem com o período de reprodução da maioria das espécies de Falconiformes na região Neotropical (del Hoyo et al, 1994;, Granzinolli et al, 2002. No caso específico do gavião-dorabo-branco, a reprodução ocorre na estação seca Thiolay, 1978apud Newton, 1979.…”
Section: -Resposta Numéricaunclassified
“…Esta observação está de acordo comPhilips & Dindal (1979) eScheibler (2001), que relatam a umidade, os invertebrados e os fungos como fatores de fragmentação e decomposição das pelotas que ficam expostas. Entretanto, o maior número de pelotas encontradas na estação seca coincide com a reprodução de B.albicaudatusGranzinolli et al, dados não publicados).O montante de pelotas analisado parece incluir todos os itens alimentares consumidos pelo gavião na área em questão. Após a amostra 182 (de acordo com a ordem cronológica de coleta) não foi encontrada nenhuma nova ocorrência de espécie/morfoespécie.…”
unclassified